Ten Lessons for Good Practice for the INHERIT Triple Win: Health, Equity, and Environmental Sustainability - Bell, Ruth; Khan, Matluba; Romeo-Velilla, Maria; Stegeman, Ingrid; Godfrey, Alba; Taylor, Timothy; Morris, George; Staatsen, Brigit; van der Vliet, Nina; Kruize, Hanneke; Anthun, Kirsti Sarheim; Lillefjell, Monica; et al. (International journal of environmental research and public health, 2019)
The world's challenges of climate change, damage to ecosystems, and social and health inequalities require changes in human behaviours at every level of organisation, among governments, business, communities, and individuals. An important question is how behaviour change can be enabled and supported at the scale and speed required. The research reported in this paper describes important lessons for good practice in changing contexts to modify behaviours for a triple win for health, equity and environmental sustainability. Authors synthesised learning from qualitative, quantitative and cost benefit evaluations of 15 case studies conducted in 12 countries in Europe. The case studies address ways of living (green spaces and energy efficient housing), moving (active transport) and consuming (healthy and sustainable diets) that support the triple win. Ten lessons for good practice were identified. These include bringing a triple win mindset to policy and practice in planning interventions, with potential to improve environmental sustainability, health and equity at the same time. The lessons for good practice are intended to support governmental and non-governmental actors, practitioners and researchers planning to work across sectors to achieve mutual benefits for health and environmental sustainability and in particular to benefit poorer and more socio-economically disadvantaged groups.
Keywords: Socioeconomic Factors; Health Equity; Climate Change; Ecosystem; co-creation; Europe; moving; behaviour change; socioekonomické faktory; rovnost ve zdraví; equity; bydlení; Evropa; living; Health Status; lidé; urban settings; Humans; Housing; health; ekosystém; zdravotní stav; klimatické změny; environmental sustainability; policy and practice; consuming